Fa’aliyah Thariqah Course review Horay Li Tahsin Maharatul Qira’ah Lada Thullab fil Madrasah al-Mutawassithah al-Islamiyah Sabilul Ulum Mayong - Amalia, Dina; Annas, Azwar (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2025)
This article discusses the effectiveness of using the course review horay method in improving students' maharah qira'ah. The research was conducted on class VIII students of Mts Sabilul Ulum Mayong in the 2024/2025 academic year. The research subjects included 32 students. The purpose of this study was to determine the students' maharah qira'ah ability, and to prove that the Course Review Horay learning method is very effective in the Arabic language learning process to improve students' maharah qira'ah. The type of research is quantitative research. The data collection techniques used were questionnaires and tests in the form of a pretest-posttest. The test results were analyzed using SPSS. Data analysis techniques used descriptive statistical analysis and inferential analysis. The findings of this study are that the course review horay method is effectively used to increase students' maharah qira'ah with a medium level of effectiveness, and the N-Gain score is 0.3822.